Clinical observations of surgical treatment of patients with Pair syndrome - I. V. Makarov; V. E. Zaitsev; D. A. Korolev; I. A. Tyumin; A. B. Petrov; E. A. Panarin; A. A. Kudashova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article provides a brief overview of the frequency and prevalence of Pair syndrome, the causes of its development, the clinical picture and diagnosis of this form of splanchnoptosis, the tactics of surgical treatment depending on the stage of the disease. There are 2 clinical cases of successful surgical treatment of chronic constipation in patients with Pair syndrome. At the same time, in the classical picture of the disease, left-sided hemicolectomy with a thick-colonic anastomosis "end to end" was performed, in a patient with concomitant diverticular disease - an extended hemicolectomy. All patients are discharged with recovery, all have an independent regular stool every 1-3 days